THE LIVED EXPERIENCES OF PARENTS OF YOUNG WOMEN WITH MULTIPLE SCLEROSIS IN IRAN - Panahi, Marzieh; Tazakori, Zahra; Karimollahi, Mansoureh (International Journal of Child, Youth and Family Studies, 2023)
Chronic illness in children causes more mental health risks for parents than for other family members. Therefore, exploring the experiences of parents who have a daughter with multiple sclerosis (MS) and presenting them to health care planners and managers can have a positive impact on community health. This phenomenological study involving 12 participants in Iran aimed to explore the experiences of parents of young women (aged 17 to 40) with MS. The data collected from semi-structured interviews were analyzed using Colaizzi’s method. Open coding resulted in 450 codes, and after several stages of analysis and integration of similar codes, five main themes containing 21 subthemes were produced. The main themes were mental distress, feeling trapped, adaptation issues, reaction to the disease, and coming to terms with the disease. This study showed that having a daughter with MS affects all dimensions of the parents’ life, and can lead to experiences that are new to them and may confuse them. These findings provide a path towards improving effective parental care for their daughters with MS, and ultimately reducing the burden of disease on the family, the health system, and the community.